The Samaritan Pentateuch and the Dead Sea Scrolls - Langlois, Michaël 1976- (Leuven Paris Bristol,CT Peeters, 2019)
Seventy years after their discovery, the Dead Sea Scrolls continue to shed light on the Samaritan Pentateuch. The textual features, orthography, script, variant readings and even theology of the Samaritan Pentateuch have parallels in various manuscripts found in the Judaean desert and copied during the Second Temple period. The fertile encounter of Samaritan and Dead Sea Scrolls studies has yielded this exceptional volume, featuring twelve contributions by some of the most respected scholars gathered at the University of Strasbourg on May 26?27, 2016. They cover such issues as scribal and editorial practices, political and religious history, textual editions and versions, palaeography and linguistics? with provocative studies challenging classical theories on the origin of the Gerizim tenth commandment or the date of the earliest Dead Sea Scrolls.
Aus dem Vorwort: "These twelve contributions have been peer-reviewed and are the outcome of an international conference held on may 26-27, 2016 at the University of Strasbourg"
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Aufsatzsammlung; Konferenzschrift -- 26.-27. Mai 2016 -- Strasbourg